2021
DOI: 10.4049/jimmunol.2000928
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia Virus Infection Inhibits Skin Dendritic Cell Migration to the Draining Lymph Node

Abstract: There is a paucity of information on dendritic cell (DC) responses to vaccinia virus (VACV), including the traffic of DCs to the draining lymph node (dLN). In this study, using a mouse model of infection, we studied skin DC migration in response to VACV and compared it with the tuberculosis vaccine Mycobacterium bovis bacille Calmette-Guérin (BCG), another live attenuated vaccine administered via the skin. In stark contrast to BCG, skin DCs did not relocate to the dLN in response to VACV. Infection with UV-ina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…We therefore next asked whether scarification-induced lymphatic capillary zippering affects the generation of protective immune responses. Despite a reduction in fluid transport following VACV scarification and the inhibition of DC migration by replication competent VACV ( Aggio et al, 2021 ), DCs do access dLNs and drive potent protective immune responses ( Loo et al, 2017 ). We sought to quantify the impact of VEGFR2 signaling on DC migration.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore next asked whether scarification-induced lymphatic capillary zippering affects the generation of protective immune responses. Despite a reduction in fluid transport following VACV scarification and the inhibition of DC migration by replication competent VACV ( Aggio et al, 2021 ), DCs do access dLNs and drive potent protective immune responses ( Loo et al, 2017 ). We sought to quantify the impact of VEGFR2 signaling on DC migration.…”
Section: Resultsmentioning
confidence: 99%
“…It has been postulated that infection of the dermal keratinocytes, fibroblasts and tissue-resident antigen-presenting cells such as monocytes, macrophages, Langerhans cells and dendritic cells might occur and migratory antigen-presenting cells could contribute to virus dissemination through the lymphatics 46 , 54 , 55 . Nonetheless, recent evidence from a mouse model of orthopoxvirus skin infection suggested that dendritic cell migration from the skin to draining lymph nodes is impaired on VACV 56 . The relocation of the virus from the skin to the lymphatics might also be supported by other mechanisms such as direct lymphatic vessel access, as observed in skin infection models of Zika virus 57 .…”
Section: Mpxv Pathogenesismentioning
confidence: 99%
“…Instead, infection is performed in the footpad skin to quantify relocation of skin DCs from that site to the dLN (the pLN). Prior results from the combined use of these models support the detection of TNF-α and IL-1α/β in infected skin with a role for TNFR-I and IL-1R-I in skin DC migration to dLNs ( 19 , 26 ). Indomethacin treatment had a visible, negative impact on BCG-mediated skin DC migration to dLNs ( Fig.…”
Section: Resultsmentioning
confidence: 79%
“…The mobilization of Ag-laden DCs from the infection site in the periphery to the dLN is needed for T cell priming. Support for this comes from observations, including our own, showing that failure or inhibition of skin DC migration from skin to dLN mutes the expansion of Ag-specific T cells in the dLN ( 19 , 26 28 ). The movement of DCs from tissue to LN is complex.…”
Section: Discussionmentioning
confidence: 91%